Efficacy of rhBMP-2/Hydroxyapatite on Sinus Floor Augmentation: A Multicenter, Randomized Controlled Clinical Trial - Kim, H.J.; Chung, J.H.; Shin, S.Y.; Shin, S.I.; Kye, S.B.; Kim, N.K.; Kwon, T.G.; Paeng, J.Y.; Kim, J.W.; Oh, O.H.; Kook, M.S.; Yang, H.J.; et al. (Journal of dental research, 2015)
The aim of this randomized single-blinded active-controlled clinical study was to evaluate the early efficacy of low-dose Escherichia coli–derived recombinant human bone morphogenetic protein 2 (rhBMP-2) soaked with hydroxyapatite granules (BMP-2/H) as compared with an inorganic bovine bone xenograft (ABX) in maxillary sinus floor augmentation. In a total of 127 subjects who were enrolled at 6 centers, maxillary sinus floors were augmented with 1 mg/mL of rhBMP-2 (0.5 to 2.0 mg per sinus) and BMP-2/H (0.5 to 2.0 g; n = 65) or with ABX alone (0.5 to 2.0 g; n = 62). Core biopsies were obtained 3 mo after the augmentation surgery and were analyzed histomorphometrically. The mean new bone formation with BMP-2/H and ABX augmentation was 16.10% ± 10.52% and 8.25% ± 9.47%, respectively. The BMP-2/H group was noninferior to the ABX group; the lower limit of the 1-sided 97.5% confidence interval for the difference between the 2 groups was calculated as 4.33%, which was greater than the prespecified noninferiority margin of −3.75%. An additional test with the Wilcoxon rank-sum test with a 2-sided 5% significance level showed that bone formation between the 2 groups was significantly different (P < 0.0001). The soft tissue and residual graft areas showed no significant differences between the groups. With regard to safety, no significant difference between the 2 groups was observed; there was no significant increase in the amount of rhBMP-2 antibody in the serum after BMP-2/H grafting. Our study suggested that low-dose Escherichia coli–derived rhBMP-2 with hydroxyapatite was effective in early stages for enhanced bone formation after maxillary sinus floor augmentation without harmful adverse events (Clinicaltrials.gov NCT01634308).